2018
DOI: 10.1088/1361-6455/aab425
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer in low-energy collisions of H with He+and H+with He in excited states

Abstract: We present a theoretical study of charge transfer in collisions of excited (n = 2, 3) hydrogen atoms with He + and in collisions of excited (n = 2, 3) helium atoms with H +. A combination of a fully quantum-mechanical method and a semi-classical approach is employed to calculate the chargeexchange cross sections at collision energies from 0.1 eV/u up to 1 keV/u. These methods are based on accurate ab initio potential energy curves and non-adiabatic couplings for the molecular ion HeH +. Charge transfer can occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…The excited deuterium (n = 2, 3)-He + CX crosssections for each of the two spin systems of helium have been recently calculated. 10 Including the channels for each of the spin systems is very important to take into account when modeling helium emission due to the long relaxation times of the metastable (See figure 1). In this work, only the cross-sections for deuterium were used since it is the main isotope used in AUG and in many other research reactors.…”
Section: Kinetic Collisional Radiative Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…The excited deuterium (n = 2, 3)-He + CX crosssections for each of the two spin systems of helium have been recently calculated. 10 Including the channels for each of the spin systems is very important to take into account when modeling helium emission due to the long relaxation times of the metastable (See figure 1). In this work, only the cross-sections for deuterium were used since it is the main isotope used in AUG and in many other research reactors.…”
Section: Kinetic Collisional Radiative Modelmentioning
confidence: 99%
“…It was found that there are small isotopic differences in the cross-sections between hydrogen, deuterium, and tritium, particularly in the low collision energy region. 10 The cross-sections for both spin systems of helium are shown in figure 2.…”
Section: Kinetic Collisional Radiative Modelmentioning
confidence: 99%
See 3 more Smart Citations